Chemical composition and potential antioxidant, anti-inflammatory, and analgesic efficacy of Cistus albidus L. - Zouhri Aziz; Bouddine Toufik; Menyiy Naoual El; El-Mernissi Yahya; Laaroussi Hassan; Chebaibi Mohamed; Amhamdi Hassan; Elharrak Abdelhay; Nafidi Hiba-Allah; Sitotaw Baye; Jardan Yousef A. Bin; Bourhia Mohammed; et al. (Acta Pharmaceutica)
This study aims to assess the chemical composition of the aqueous extract of Cistus albidus L. leaves, as well as the potential of aqueous and hydroethanol extracts of the leaves and seeds as analgesic, anti--inflammatory, and antioxidant agents. The contents of phenolics and inorganic constituents were determined in C. albidus seeds and leaves; antioxidant capacity was assessed by 3 complementary and diverse tests. The carrageenan-induced paw edema technique was used to investigate the anti-inflammatory effect in vivo, and albumin denaturation to evaluate the anti-inflammatory effect in vitro. The acetic acid-induced contortion test, the tail-flick test, and the plantar test were used to assess the analgesic effi cacy in vivo.